From the Editor - Judith A. Holton (Grounded Theory Review: An International Journal)
This issue offers a balance of papers devoted to substantive theories and to methodological aspects of classic grounded theory (CGT). We are pleased to include another of Dr. Glaser’s early papers; this one, first published in 1963, offers the reader an example of Glaser’s early development of CGT using quantitative data. More than 40 years after its first publication, the paper is valuable not only in illuminating those early roots of grounded theory but also in illustrating the enduring grab of a good GT. Many novice researchers and PhD candidates will readily recognize Glaser’s theory of attraction, autonomy and reciprocity in their relationships with supervisors.